2022
DOI: 10.1111/ijfs.15555
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in plant‐based compounds for mitigation of mycotoxin contamination in food products: current status, challenges and perspectives

Abstract: There are numerous strategies to control the growth of mycotoxigenic fungi and reduce mycotoxins in food, including physical, chemical and biological treatments. However, consumers prefer organic food and natural inhibitors because they are biodegradable and safe for human and animal health. This review summarises the current advances in plant-based compounds to mitigate contamination of food products by mycotoxigenic fungi and their toxins. In addition, a clear understanding of the roles of plant-based extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 103 publications
0
21
0
Order By: Relevance
“…In recent years, there has been a tremendous increase in the demand for new methods of controlling or combating foodborne pathogens. Consequently, packaging with enhanced features for food is crucial to ensure the safety of food and maintain food quality [1,2]. The concept of smart food packaging was developed in response to consumer demands for products that are safer and more natural with a prolonged shelf life, lower cost and greater convenience during storage and transportation [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a tremendous increase in the demand for new methods of controlling or combating foodborne pathogens. Consequently, packaging with enhanced features for food is crucial to ensure the safety of food and maintain food quality [1,2]. The concept of smart food packaging was developed in response to consumer demands for products that are safer and more natural with a prolonged shelf life, lower cost and greater convenience during storage and transportation [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, food products contaminated by mycotoxins have been a critical problem regarding global food safety (Jafarzadeh et al ., 2022). These toxins are fungi secondary metabolites produced by Fusarium , Aspergillus , Penicillium and Alternaria (Mokhtarian et al ., 2020; De Souza et al ., 2021; Heshmati et al ., 2021; Jafari et al ., 2021; Nešić et al ., 2021; Pires et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…By collating the literature and reports in the past years, the United Nations Food and Agriculture Organization reported that about 25% of food crops are contaminated by mycotoxins (Eskola et al., 2020). Once the contaminants in food enter the food chain, they are difficult to be removed because of their chemical and thermally stability (Jafarzadeh et al., 2022; Parra‐Arroyo et al., 2022). Thus, development of simple, rapid, low‐cost, and on‐site detection techniques for monitoring mycotoxins throughout the whole food chain is urgently needed.…”
Section: Introductionmentioning
confidence: 99%